2016
DOI: 10.1590/1413-785220162404156874
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity Impact on Social Functioning After Hip Fracture: The Role of Rehabilitation

Abstract: Objective: To analyze the impact of rehabilitation treatment on social functioning in elderly patients after hip fracture during a rehabilitation program.Methods:This study included 203 patients with hip fracture. Four groups were analyzed on rehabilitation: Group 1, at admission, Group 2, at discharge, Group 3, three months after discharge and Group 4, six months after discharge. The analyzed parameters included: musculoskeletal, neurological and cognitive impairments. Impairment severity was graded by cumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It is know that comorbidity is frequently present in elderly [12], but so far in Serbia and countries in transition, there are a few studies dealing with physical health and needs on the representative level. Thus, mainly published studies are clinical investigations and case studies [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It is know that comorbidity is frequently present in elderly [12], but so far in Serbia and countries in transition, there are a few studies dealing with physical health and needs on the representative level. Thus, mainly published studies are clinical investigations and case studies [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The Charlson Comorbidity Index (CCI) predicts mortality, morbidity, and postoperative complications after a hip fracture [ 15 , 16 , 17 ]. Recent studies [ 18 , 19 ] on hip fracture patients undergoing intense inpatient rehabilitation showed that moderate to severe comorbidity and communication are prevalent and predict rehabilitation failure.…”
Section: Methodsmentioning
confidence: 99%